What is green Innovation? A quantitative literature review - Tim Schiederig; Frank Tietze; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2011)
The importance of green innovation management is growing in practice and academia likewise. To our knowledge, a recent and comprehensive literature review is lacking. In this paper we contribute to a clarification of the concept green innovation and provide an overview of the existing body of literature in the field of green innovations identifying the most active scholars, institutions and relevant publications. We find that the three different notions of green, eco/ecological and environmental innovation are used largely synonymously while the notion of sustainable innovation broadens the concept and includes a social dimension. We find further that the most active scholars are situated in Europe (i.e. Netherlands, Italy and Germany) and identified three innovation management journals leading the field.
Keywords: 650; Innovation management; green innovations; eco innovations; environmental innovations; sustainable innovations; literature review